مهارة ادارة الوقت وعلاقتها بمستوى الطموح الأكاديمي - كربوع, اسماء (University of Eloued جامعة الوادي, 2023)
ملخص الدراسة باللغة العربية تهدف الدراسة الحالية الى معرفة العلاقة بين مهارة إدارة الوقت ومستوى الطموح الاكاديمي لدى تلاميذ اولى ثانوي وقد استخدمت الدراسة المنهج وصفي الارتباطي ومن اجل الحصول على البيانات اعتمدت الدراسة على مقياس إدارة الوقت ومقياس مستوى الطموح وطبقت الدراسة على عينة بلغت 150 تلميذ من الطور الثانوي بولاية الوادي وتم اختيارها بطريقة العشوائية البسيطة وتمت معالجة إحصائية باستخدام برنامج الاحصائي للعلوم الاجتماعية spss وتوصلت الدراسة الى نتائج التالية: -لا توجد علاقة ارتباطية دالة إحصائية بين مهارة الوقت ومستوى الطموح الاكاديمي لدى تلاميذ أولى ثانوي -لا توجد فروق دالة إحصائية بين الجنسين من تلاميذ أولى ثانوي في مقياس مهارة إدارة الوقت. -لا توجد فروق إحصائية بين الذكور والاناث من تلاميذ أولى ثانوي في مقياس مستوى الطموح. -لا توجد فروق دالة إحصائية بين تلاميذ أولى ثانوي في مقياس مهارة إدارة الوقت تبعا كشعبة دراسة (علوم تكنولوجيا والاداب). -لا توجد فروق دالة إحصائية بين تلاميذ أولى ثانوي في مقياس مستوى الطموح تبعا لشعبة الدراسة (علوم التكنولوجيا والآداب).   ملخص الدراسة باللغة الأجنبية The current study aims to know the relationship between the skill of time management and the level of academic ambition among first secondary students. The study used the descriptive and relational approach. In order to obtain data, the study relied on the time management scale and the level of ambition scale. The study was applied to a sample of 150 students from the secondary stage in El Wadi state. It was chosen in a simple random way, and it was statistically processed using the statistical program for social sciences spss, and the study reached the following results: - There is no statistically significant correlation between time skill and the level of academic ambition among first secondary students - There are no statistically significant differences between the sexes of first secondary students in the time management skill scale. - There are no statistical differences between males and females of first secondary students in the level of ambition scale. - There are no statistically significant differences between first secondary students in the measure of time management skill according to the study division (Technology and Arts Sciences). - There are no statistically significant differences between first secondary students in the level of ambition scale, according to the study division (technology and arts sciences).
تخصص علم نفس